Aberrant Hepatic Methionine Metabolism and Gene Methylation in the Pathogenesis and Treatment of Alcoholic Steatohepatitis - Charles H. Halsted; Valentina Medici (International Journal of Hepatology)
The pathogenesis of alcoholic steatohepatitis (ASH) involves ethanol-induced aberrations in hepatic methionine metabolism that decrease levels of S-adenosylmethionine (SAM), a compound which regulates the synthesis of the antioxidant glutathione and is the principal methyl donor in the epigenetic regulation of genes relevant to liver injury. The present paper describes the effects of ethanol on the hepatic methionine cycle, followed by evidence for the central role of reduced SAM in the pathogenesis of ASH according to clinical data and experiments in ethanol-fed animals and in cell models. The efficacy of supplemental SAM in the prevention of ASH in animal models and in the clinical treatment of ASH will be discussed.